LDAP in the Solaris™ Operating Environment: Deploying Secure Directory Services - Haines, Michael (Prentice Hall PTR, 2011)
LDAP in the Solaris Operating Environment is a follow-on to the Sun BluePrints book Solaris and LDAP Naming Services, and describes the significant improvements to the Solaris LDAP client and directory server. Deploying the Solaris Secured LDAP Client is covered in detail. This Sun BluePrints book introduces NIS/NIS+ migration tools and techniques to aid in the transition to an LDAP-based naming service. Troubleshooting tips, examples of extending Solaris authentication methods, and examples of extending Solaris authentication methods using the Pluggable Authentication Module (PAM) framework are provided.